2009
DOI: 10.1128/cvi.00151-09
|View full text |Cite
|
Sign up to set email alerts
|

Assessment ofMycobacterium tuberculosisOmpATb as a Novel Antigen for the Diagnosis of Bovine Tuberculosis

Abstract: In the search for better tools to control bovine tuberculosis, the development of diagnostic tests with improved specificity and sensitivity has a high priority. We chose to search for novel immunodiagnostic reagents. In this study, Rv0899 (outer membrane protein A of Mycobacterium tuberculosis [OmpATb]) was evaluated as a stimulation antigen in a gamma interferon (IFN-␥) release assay to diagnose bovine tuberculosis. OmpATb induced IFN-␥ responses in cattle experimentally infected with M. bovis as early and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Therefore, a wider range of antigens in addition to ESAT‐6 and CFP‐10 is needed for improving the sensitivity of specific antigen‐based IFN‐γ assays. In recent studies, promising antigen combinations for the IFN‐γ assay resulting in improved sensitivity and specificity have been described (Cockle et al., 2006; Sidders et al., 2008; Schiller et al., 2009b). Importantly, Rv3615c and OmpATb were found to detect cattle with confirmed bTB but not responding to E/C.…”
Section: Current Testing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a wider range of antigens in addition to ESAT‐6 and CFP‐10 is needed for improving the sensitivity of specific antigen‐based IFN‐γ assays. In recent studies, promising antigen combinations for the IFN‐γ assay resulting in improved sensitivity and specificity have been described (Cockle et al., 2006; Sidders et al., 2008; Schiller et al., 2009b). Importantly, Rv3615c and OmpATb were found to detect cattle with confirmed bTB but not responding to E/C.…”
Section: Current Testing Strategiesmentioning
confidence: 99%
“…Changes required for the IFN‐γ assay to overcome its current disadvantages and to allow its use as individual animal test comprise improvements of specificity, overall test accuracy and ease of use, in addition to cost reductions. New antigen combinations have been found which complement the current lead diagnostic antigens ESAT‐6 and CFP‐10 and result in superior sensitivity, specificity, and predictive values compared to PPD‐based tests (Sidders et al., 2008; Schiller et al., 2009b; Vordermeier et al., 2009). Interestingly, recent data, using relatively small sample numbers that need to be confirmed in larger trials, indicate that even ESAT‐6 and CFP‐10 alone (without further antigens) could result in superior performance of the IFN‐γ assay compared to that of CCT.…”
Section: Options For Future Control Strategiesmentioning
confidence: 99%
“…Several antigens have shown considerable promise in existing and emerging diagnostic assays (e.g. MPB70, MPB83, ESAT6, CFP10, and OmpTb) [9-12]. However, cross-reactivity with other mycobacterial species [13,14] and variation in the immune response from animal to animal [15,16] continues to hamper improved diagnostic specificity [3].…”
Section: Introductionmentioning
confidence: 99%
“…No single antigen has, thus far, been identified that elicits a response in all animals during different stages of infection. As reported in a 2009 review, 15 many infected animals are missed with assays based on the use of a single antigen. Attempts to increase the sensitivity of the assay using multiple antigens showed this approach has the potential of increasing the ability to detect more infected animals.…”
mentioning
confidence: 99%